Analisis Hubungan Getaran dan Kekasaran Permukaan pada Proses Pembubutan Baja ST60 - Haradat Tahrir Algaza; Robert Napitupulu; Erwansyah Erwansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study aims to analyze the relationship between vibration and surface roughness in the turning process of ST 60 steel. The turning process was carried out by varying machining parameters, namely depth of cut, spindle speed, and feed rate. An experimental method was employed using eight combinations of cutting parameters. The material used was cylindrical ST 60 steel. Vibration measurements were performed using a VibraPort 80, while surface roughness measurements were conducted using a Mitutoyo SJ-210 surface roughness tester. The results show that workpiece number 1 produced the best surface quality with a surface roughness (Ra) value of 1.42 µm. In contrast, workpiece number 8 exhibited the poorest surface quality with an Ra value of 3.12 µm. The differences in surface quality were influenced by the combination of turning parameters that led to increased vibration during the cutting process. These results indicate that vibration plays an important role in determining the final surface quality. Therefore, proper control of turning parameters is required to minimize vibration and achieve optimal surface quality in the turning of ST 60 steel.